2018
DOI: 10.1103/physrevlett.120.042003
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Science with Generative Adversarial Networks: An Application to 3D Particle Showers in Multilayer Calorimeters

Abstract: Physicists at the Large Hadron Collider (LHC) rely on detailed simulations of particle collisions to build expectations of what experimental data may look like under different theoretical modeling assumptions. Petabytes of simulated data are needed to develop analysis techniques, though they are expensive to generate using existing algorithms and computing resources. The modeling of detectors and the precise description of particle cascades as they interact with the material in the calorimeter are the most com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
171
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(172 citation statements)
references
References 32 publications
1
171
0
Order By: Relevance
“…A challenge for assessing previous GAN applications in HEP is that they have been designed to model high-dimensional feature spaces that are difficult to visualize and study [11][12][13][14][15][16][17][18][19][20][21]. The mass distribution example presented here provides a concrete testing ground to study GAN approaches where quantitative agreement can be studied and achieved using existing techniques.…”
Section: Machine Learning Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A challenge for assessing previous GAN applications in HEP is that they have been designed to model high-dimensional feature spaces that are difficult to visualize and study [11][12][13][14][15][16][17][18][19][20][21]. The mass distribution example presented here provides a concrete testing ground to study GAN approaches where quantitative agreement can be studied and achieved using existing techniques.…”
Section: Machine Learning Resultsmentioning
confidence: 99%
“…2). GANs have also been studied in HEP and show great promise for accelerating simulations [11][12][13][14][15][16][17][18][19][20][21] and may also be useful for other tasks such as sampling from the space of effective field theory models [22]. In the context of QCD factorization studied in this paper, the GAN will learn the probability distribution of the jet mass given the jet kinematics and any other useful information.…”
Section: Introductionmentioning
confidence: 99%
“…In [78] the feasibility of deep generation model in high-quality, fast and electromagnetic calorimeter simulation is further studied. It was found that although it is difficult to accurately simulate the whole phase space with deep generation model, this method can reproduce many simulation properties of the detector and can accelerate the simulation of calorimeter by 100,000 times.…”
Section: Jet Taggingmentioning
confidence: 99%
“…For example, models of lake temperature that combine neural networks with loss functions consistent with known physical mechanisms perform better than physical models and neural networks applied alone (Karpatne et al 2017). Similarly, generative adversarial networks with loss functions that encourage mass-balance have expedited electromagnetic calorimeter data generation from the Large Hadron Collider (Paganini et al 2018;Radovic et al 2018). Convolutional neural networks also have been successfully deployed in population genetics to make inferences about introgression, recombination, selection, and population sizes (Flagel et al 2018).…”
Section: Related Work Neural Networkmentioning
confidence: 99%